Static output feedback H2/H∞ control with spectrum constraints for stochastic systems subject to multiplicative noises. Issue 3 (21st September 2018) - Ma, Pingping; Zhu, Zhengmao; Sheng, Li
ABSTRACT: This paper investigates the problem of static output feedbackH 2 / H ∞ control with spectrum constraints for linear continuous-time stochastic systems with state dependent noises. By using the spectrum technique, the notion ofD ( − β, − α ) stability for continuous-time stochastic systems is proposed. Subsequently, the design method of the static output feedback controller is presented by solving a set of linear matrix inequalities. UnderD ( − β, − α ) stability, a sufficient condition for the existence of stochasticH 2 / H ∞ control is derived, which transforms the problem ofH 2 / H ∞ control into a convex optimization problem. Finally, a numerical example is given to show the effectiveness of the obtained results.